Infant Feeding Alters the Longitudinal Impact of Birth Mode on the Development of the Gut Microbiota in the First Year of Life - Coker, Modupe O.; Laue, Hannah E.; Hoen, Anne G.; Hilliard, Margaret; Dade, Erika; Li, Zhigang; Palys, Thomas; Morrison, Hilary G.; Baker, Emily; Karagas, Margaret R.; Madan, Juliette C. (Frontiers in Microbiology, 2021)
Caesarean-delivered (CD) infants harbor a distinct gut microbiome from vaginally-delivered (VD) infants, however during infancy, the most important driver of infant gut microbial colonization is infant feeding. Earlier studies have shown that breastfeeding is associated with higher levels of health promoting bacteria such and Bifidobacterium and Bacteroides via modulation of the immune system, and production of metabolites. As the infant gut matures and solid foods are introduced, it is unclear whether longer duration of breast feeding restore loss of beneficial taxa within the intestinal microbiota of operatively-delivered infants. Within the New Hampshire Birth Cohort Study, we evaluated the longitudinal effect of delivery mode and infant feeding on the taxonomic composition and functional capacity of developing gut microbiota in the 1st year of life. Microbiota of 500 stool samples collected between 6 weeks and 12 months of age (from 229 infants) were characterized by 16S ribosomal RNA sequencing. Shotgun metagenomic sequencing was also performed on 350 samples collected at either 6 weeks or 12 months of age. Among participants, 28% were Caesarean-delivered (CD) infants and most (95%) initiated breastfeeding within the first six months of life, with 26% exclusively-breastfed and 69% mixed-fed (breast milk and formula), in addition to complementary foods by age 1. Alpha (within-sample) diversity was significantly lower in CD infants compared to vaginally-delivered (VD) infants (P<0.05) throughout the study period. Bacterial community composition clustering by both delivery mode and feeding duration at 1 year of age revealed that CD infants who were breast fed for <6 months were more dissimilar to VD infants than CD infants who breast fed for >6 months. We observed that breastfeeding modified the longitudinal impact of delivery mode on the taxonomic composition of the microbiota by 1 year of age, with an observed increase in abundance of Bacteroides fragilis and Lactobacillus with longer duration of breastfeeding among CD infants while there was an increase in Faecalibacterium for VD infants. Our findings confirms that duration of breastfeeding plays a critical role in restoring a health-promoting microbiome, and clarifies mechanisms behind the association between breast milk exposure and health outcomes in early life.